GhMYB7 promotes secondary wall cellulose deposition in cotton fibres by regulating GhCesA gene expression through three distinct cis‐elements. Issue 4 (4th August 2021) - Huang, Junfeng; Chen, Feng; Guo, Yanjun; Gan, Xinli; Yang, Mingming; Zeng, Wei; Persson, Staffan; Li, Juan; Xu, Wenliang
Summary: Cotton fibre is the most important source for natural textiles. The secondary cell walls (SCWs) of mature cotton fibres contain the highest proportion of cellulose content (> 90%) in any plant. The onset and progression of SCW cellulose synthesis need to be tightly controlled to balance fibre elongation and cell wall deposition. However, regulatory mechanisms that control cellulose synthesis during cotton fibre growth remain elusive. Here, we conducted genetic and functional analyses demonstrating that the R2R3‐MYB GhMYB7 controls cotton fibre cellulose synthesis. Overexpression of GhMYB7 in cotton sped up SCW cellulose biosynthesis in fibre cells, and led to shorter fibres with thicker walls. By contrast, RNA interference (RNAi) silencing of GhMYB7 delayed fibre SCW cellulose synthesis and resulted in elongated fibres with thinner walls. Furthermore, we demonstrated that GhMYB7 regulated cotton fibre SCW cellulose synthases by directly binding to three distinct cis ‐elements in the respective GhCesA4, GhCesA7 and GhCesA8 promoters. We found that this regulatory mechanism of cellulose synthesis was 'hi‐jacked' also by other GhMYBs. Together, our findings uncover a hitherto‐unknown mechanism that cotton fibre employs to regulate SCW cellulose synthesis. Our results also provide a strategy for genetic improvement of SCW thickness of cotton fibre.